ANALISIS PENGEMBANGAN DESTINASI WISATA RELIGI PADA ISLAMIC CENTER KALIMANTAN TIMUR DI KOTA SAMARINDA - Wahyutika Chandra Kasih (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2019)
The result of this research, tourism object manager has not yet fully planned development in the field of tourism. Attraction, amenities and accesibility development efforts ned to be made because religios destination of Islamic Center East Kalimantan has a great potential. SO Strategy can be utilized by tourism object manager is 1) manage and optimize the potential of tourist attraction, 2) improve the performance of tourism managers 3) organizing event or tourism routine activities. Supporting factors for developmnet isthe role of goverment, it has a easy coordination between parties, and already have good facilities and infrastructure. Inhibiting factor for development is lack of goverment funding and less solid human resources.